Orofacial consequences of systemic sclerosis: A systematic review. Issue 1 (February 2018) - Smirani, Rawen; Poursac, Nicolas; Naveau, Adrien; Schaeverbeke, Thierry; Devillard, Raphaël; Truchetet, Marie-Elise
Orofacial involvement is common and often understated in the treatment clinical guidelines of systemic sclerosis. It impairs daily life by having repercussions on comfort, nutrition, aesthetics and self-confidence. This review aimed at describing exhaustively the different orofacial consequences of systemic sclerosis. A systematic search was conducted using four databases (PubMed, Cochrane Library, Dentistry & Oral Sciences Source and SCOPUS) up to December 2016 according to the Preferred Reporting Items for Systematic Reviews and Meta-analyses. Grey literature and hand search were also included. To be eligible for the inclusion, studies needed to meet the following criteria: randomised controlled trials, cross-sectional studies, case-control studies, pilot studies or cohort studies and full text available in English or French, with abstract. The studies had to concern at least 30 patients suffering from systemic sclerosis and having clinical and radiological oropharyngeal examination. The diagnosis of systemic sclerosis had to be determined according to precise recommendations; the retrieved oropharyngeal manifestations had to affect hard or soft tissues of the mouth and/or pharynx and needed to be evaluated with clinical measures. Study selection, risk bias assessment (Newcastle–Ottawa scale) and data extraction were performed by two independent reviewers. The retrieved features were microstomia and xerostomia associated with real hyposialia, temporomandibular joint symptoms, high caries experience, periodontal diseases as well as an increased risk of oral cavity and pharynx cancer. Early diagnosis enabling early management, prevention and oral hygiene is the key to avoid complicated and invasive procedures. Studies with higher level of evidence remain necessary to create standardised protocols.